2011
DOI: 10.1085/jgp.201110679
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the Cx26 hemichannel: Evaluation of structural models with Brownian dynamics

Abstract: The recently published crystal structure of the Cx26 gap junction channel provides a unique opportunity for elucidation of the structure of the conductive connexin pore and the molecular determinants of its ion permeation properties (conductance, current–voltage [I-V] relations, and charge selectivity). However, the crystal structure was incomplete, most notably lacking the coordinates of the N-terminal methionine residue, which resides within the pore, and also lacking two cytosolic domains. To allow computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(146 citation statements)
references
References 93 publications
(185 reference statements)
5
137
1
2
Order By: Relevance
“…Nevertheless, the initial events seen in the present simulations indicate that the subsequent rearrangements of the network of electrostatic interactions below D50-K61 are among the steps that enhance the probability of transition to a Ca 2+ -induced closed state. The previously equilibrated Cx26 hemichannel and other connexin structural models also associate these residues with electrostatic interactions in the open conformation (21,22).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, the initial events seen in the present simulations indicate that the subsequent rearrangements of the network of electrostatic interactions below D50-K61 are among the steps that enhance the probability of transition to a Ca 2+ -induced closed state. The previously equilibrated Cx26 hemichannel and other connexin structural models also associate these residues with electrostatic interactions in the open conformation (21,22).…”
Section: Discussionmentioning
confidence: 87%
“…We proposed that this interaction is disrupted with increasing extracellular Ca 2+ concentrations, and that this may constitute the initial reaction for hemichannel closure (17). To gain further insights into the gating mechanism mediated by Ca 2+ disruption of the D50-K61 interaction, we performed molecular dynamics simulations, building on previously well-established equilibrated structures of Cx26 hemichannels (22,23). We observed that K + ions accumulate near the extracellular entrance of the pore where several negatively charged residues are located, including D50 (23).…”
Section: Calcium Disrupts Electrostatic Network At the Extracellularmentioning
confidence: 99%
“…Cx30 shares 76% sequence identity with Cx26 (Grifa et al, 1999), and although the crystal structure of Cx30 has not yet been resolved, the crystal structure of Cx26 has elucidated that the N-terminal tail lines the gap junction channel pore, creating a funnel that restricts channel selectivity based on molecular size, flexibility, charge and charge distribution (Harris, 2007;Kwon et al, 2011;Maeda et al, 2009). In the nonsensory cells of the inner ear, Cx26 and Cx30 intermix to form heteromeric and heterotypic channels (Ahmad et al, 2003;Forge et al, 2003;Marziano et al, 2003;Yum et al, 2007) and are suggested to form functional hemichannels (Gossman and Zhao, 2008;Zhao et al, 2005).…”
Section: The T5m Mutant Linked To Non-syndromic Hearing Lossmentioning
confidence: 99%
“…Journal of Cell Science (2014Science ( ) 127, 1751Science ( -1764Science ( doi:10.1242 second transmembrane domain also lines the channel pore and is involved in intraconnexin interactions with other domains, including the N-terminus, that dictate specific protein conformation (Kwon et al, 2011;Maeda et al, 2009). By analogy, it is possible that the A88V Cx30 mutation affects protein folding and stability, and alters important interactions, moving the N-terminal domain away from the cytoplasmic entrance of the pore (Kwon et al, 2011;Maeda et al, 2009) to favor abnormal hemichannel activity.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation